2021
DOI: 10.7759/cureus.19894
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Gallstones in Young Patients Under the Age of 30 Years

Abstract: IntroductionGallstones are deposits of digestive fluid that is hardened into small pellets. Gallstones can be symptomatic or asymptomatic. The present study assessed the sociodemographic and clinical characteristics of patients under the age of 30 years old with symptomatic gallstones. MethodologyA prospective, observational study was conducted at Surgical Unit-3, at Jinnah Postgraduate Medical Centre (JPMC), Pakistan, from July 2020 to July 2021. All patients suspected of having gallstone disease underwent ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In addition, it was found that 114 people were overweight, while 108 (51.43%) had elevated triglyceride and 115 (54.76%) had high cholesterol levels. The results showed that young people are susceptible to symptomatic gallstones, and the rate of this disease was significantly higher in women, in patients with high cholesterol and triglyceride levels and abnormal body mass index (BMI) [3] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was found that 114 people were overweight, while 108 (51.43%) had elevated triglyceride and 115 (54.76%) had high cholesterol levels. The results showed that young people are susceptible to symptomatic gallstones, and the rate of this disease was significantly higher in women, in patients with high cholesterol and triglyceride levels and abnormal body mass index (BMI) [3] .…”
Section: Discussionmentioning
confidence: 99%
“…These stones are formed in the gallbladder and biliary tract [2] and can be symptomatic or asymptomatic. Their size can range from grains of sand to golf balls [3] and can be easily detected by ultrasound [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in France showed that the prevalence of gallstone in adolescent population is higher than previously thought Reports of childhood obesity and the use of oral contraceptives, remains latent as strong independent risk factors for gallstone disease, where reports have consistently remained in recent years [5,6]. Recent studies have indicated that cholelithiasis is strongly related to body mass index [7]. This may be due to increased fat intake and less physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for higher risk of developing cholelithiasis probably has to do with hormonal and reproductive factors, i.e. oral contraceptives or hormone therapy taken by women as well as pregnancy [19]. Naturally occurring menopause around the age of 49 is associated with the start of hormone replacement therapy [MHT].…”
Section: Introductionmentioning
confidence: 99%